2003
DOI: 10.1109/tbme.2003.809495
|View full text |Cite
|
Sign up to set email alerts
|

A pseudojoint estimation of time delay and scale factor for m-wave analysis

Abstract: A pseudojoint estimation of time scale and time delay between an unknown deterministic transient type signal and a reference signal is proposed. The method is based on the separation between the estimations of the two dependent parameters. The time autocorrelation function (TACF) preserves the time scale and is invariant with respect to the time delay between the signals. The time scale factor can, thus, be estimated independently from time delay using the TACFs of the two signals. After estimating the time sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Most of the results showed decrease in muscle fiber conduction velocity and reduction in mean/median frequency during the muscle fatigue process [13]. Several studies confirmed that the lengths of stimulated muscle could affect the spectral, temporal, and amplitude features of evoked EMG [13,14,15]. Our previous study indicated that the amplitudes of the evoked EMG of the quadriceps muscle in electrically elicited muscle contractions were significantly different when the knee angle was varied [16].…”
Section: Introductionmentioning
confidence: 92%
“…Most of the results showed decrease in muscle fiber conduction velocity and reduction in mean/median frequency during the muscle fatigue process [13]. Several studies confirmed that the lengths of stimulated muscle could affect the spectral, temporal, and amplitude features of evoked EMG [13,14,15]. Our previous study indicated that the amplitudes of the evoked EMG of the quadriceps muscle in electrically elicited muscle contractions were significantly different when the knee angle was varied [16].…”
Section: Introductionmentioning
confidence: 92%
“…For example, spectral compression can be assessed through estimation of the scaling factor between the power spectrum of the signal at the beginning and at the end of the contraction, using other methods than characteristic frequencies (LATERZA et al, 1998). Equivalently, the scaling factor can be computed between the autocorrelation functions of signal segments detected during the contraction, in the case of detection of surface EMG signals elicited by electrical stimulation, the signal itself (the Mwave) scales during time, and thus scale factor estimation can be applied directly to the M-waves (Lo CONTE et al, 1994;LO CONTE and MERLETTI, 1995;MUHAMMAD et al, 2003). The same concepts apply for the analysis of single MU action potentials.…”
Section: P(f) = -~ Gmentioning
confidence: 99%
“…An example of such a case is the detection of two M-waves from different locations along the muscle fibres. The M-wave detected from the most distant location from the innervation zone will be scaled and delayed with respect to the first one owing to the distribution of CVs of the contributing MUs (MUHAMMAD et al, 2003).…”
mentioning
confidence: 99%
“…If the signal to be detected is perfectly known and the noise is stationary with zero-mean and white power spectral density, the optimal detector is the matched filter (MF) which maximizes the output signal-to-noise ratio (SNR) [1]. However, the signal may not be known in many practical applications, such as underwater acoustics [2][3][4][5], seismology [6][7][8][9], neurophysiology [10,11], and passive radar [12][13][14][15][16]. Consider for example passive radar.…”
Section: Introductionmentioning
confidence: 99%